2017
DOI: 10.1038/oncsis.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-TRIM28 complex promotes the Warburg effect and hepatocellular carcinoma progression by targeting FBP1 for degradation

Abstract: Hepatocellular carcinoma (HCC) is one of the leading cause of cancer death in the world. Fructose-1,6-biphosphatase (FBP1), a rate-limiting enzyme in gluconeogenesis, has been identified recently as a tumor suppressor in HCC and other cancer types. In this study, we demonstrated that the tripartite motif-containing protein 28 (TRIM28) binds directly to and promotes FBP1 for ubiquitination and degradation. MAGE-A3 and MAGE-C2, which are known to be overexpressed in HCC, can enhance TRIM28-dependent degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 44 publications
3
88
1
Order By: Relevance
“…1A; Supplementary Table S2; ref. 16). Given that IQGAP1 is a scaffold protein that plays an important role in activation of the RAF–MEK–ERK pathway and tumorigenesis in PDAC (8, 17), we were interested in exploring the molecular basis and biological impact of the interaction between FBP1 and IQGAP1 in PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…1A; Supplementary Table S2; ref. 16). Given that IQGAP1 is a scaffold protein that plays an important role in activation of the RAF–MEK–ERK pathway and tumorigenesis in PDAC (8, 17), we were interested in exploring the molecular basis and biological impact of the interaction between FBP1 and IQGAP1 in PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, MAGE-A3/6 drives cellular transformation, tumor growth, and metastasis [10,16,18]. Specifically, MAGE-A3/6 drives ubiquitination and degradation of two key metabolic enzymes and tumor suppressors, 5 0 adenosine monophosphate-activated protein kinase (AMPK) and fructose-1,6-bisphosphatase 1 (FBP1), by the TRIM28 E3 ubiquitin ligase [10,[19][20][21][22]. Specifically, MAGE-A3/6 drives ubiquitination and degradation of two key metabolic enzymes and tumor suppressors, 5 0 adenosine monophosphate-activated protein kinase (AMPK) and fructose-1,6-bisphosphatase 1 (FBP1), by the TRIM28 E3 ubiquitin ligase [10,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, MAGE-A3/6 drives ubiquitination and degradation of two key metabolic enzymes and tumor suppressors, 5 0 adenosine monophosphate-activated protein kinase (AMPK) and fructose-1,6-bisphosphatase 1 (FBP1), by the TRIM28 E3 ubiquitin ligase [10,[19][20][21][22]. Thus, MAGE-A3/6 promotes glycolysis and the Warburg effect through degradation of FBP1 [19]. This reaction is a rate-limiting step in gluconeogenesis and inhibits glycolysis and the Warburg effect [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that Tat expression was inversely proportional to KAP1 expression level suggesting that KAP1-mediated repression of Tat function results from Tat degradation. KAP1 has been shown to promote proteasomal degradation of targets proteins by its RBCC domain (53)(54)(55). Surprisingly, we observed that Tat degradation was not sensitive to RBCC depletion but mediated by the PHD and the Bromo domains of KAP1.…”
Section: Discussionmentioning
confidence: 57%